QURAN LEARNING STRATEGY AT THE DAARUL ARQOM SAWAHAN MUHAMMADIYAH BOARDING SCHOOL - Surya, Hanif Bahaudin Dzakir Putra; Dartim, Dartim (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Every Muslim uses the Koran as a guidance in life, although many Muslims are still illiterate. Al-Qur'an education is therefore required in the community as well as in Islamic boarding schools and formal schools. The purpose of this study is to describe: 1. Muhammadiyah Daarul Arqom Islamic Boarding School's Al Qur'an Learning Strategy. 2. Factors that Encourage and Discourage Muhammadiyah Daarul Arqom Islamic Boarding School to Use Al-Qur'an Learning Strategies. Data is gathered using a qualitative descriptive technique that includes observation, interviews, and documentation. The study's findings indicate that: 1. The Muhammadiyah Daarul Arqom Islamic boarding school uses a three-stage approach to teaching the Al-Qur'an: preparation, execution, and assessment 2). Supporting factors that occur in learning the Qur'an at the Muhammadiyah Daarul Arqom Islamic boarding school, namely: a) adequate classroom facilities, mosques and study places, b) good communication, carried out by ustadz with ustadz, ustadz with people old students, and ustadz with students. c) Motivation, which the ustadz gives to the students. The inhibiting factors that occur are: a) Laziness within the students, b) friends, when the students see their friends playing, the students are interested in following them.